PS7:133 Exposure-response modelling and exposure-safety modelling analyses in two phase ii studies of atacicept in sle. (21st March 2018) - Papasouliotis, O; Yalkinoglu, O; Vazquez Mateo, C; Wax, S; Kao, A; Chang, P; Fleuranceau-Morel, P; Mahnke, L
Abstract : Purpose: Atacicept targets the B-cell stimulating factors BLyS and APRIL, and has been shown to reduce SLE disease activity. Methods: APRIL-SLE (NCT00624338 ) and ADDRESS II (NCT01972568 ) were phase II, multicenter studies in patients (pts) with autoantibody-positive SLE randomised (1:1:1) to weekly SC injections of atacicept (75 or 150 mg) or placebo (PBO). In APRIL-SLE, pts had BILAG A/B flare at Screening that was reduced to BILAG C/D before randomization using corticosteroids; the primary endpoint was BILAG A/B flare over 52 weeks. In ADDRESS II, pts had SLEDAI-2K≥6 at Screening; the primary endpoint was SRI-4 response at Week 24. SLE responder index (SRI)−6 response was analysed post-hoc in high disease activity (HDA; SLEDAI-2K≥10) pts. Population pharmacokinetic (PK) model-derived exposure vs the probability of response (BILAG A/B flare, SRI-4, SRI-6), exploratory analysis of exposure vs safety, and population model simulations of serum IgG were analysed. Results: Exposure-response modelling suggests a relationship between atacicept exposure and SLE clinical response [figure 1], including serum IgG changes from baseline. The optimal atacicept exposure was AUCtau, ss ≥ 1 mg.hr/mL, which is more achievable with weekly SC doses of atacicept 150 mg than 75 mg across a range of body weights. Body weight-based dosing is unlikely to offer any value over a fixed 150 mg dose, based on comparable predicted clinical response. In HDA pts, greater reductions in serum IgG from baseline corresponded to a higher probability of SRI-6 response. Greater IgG reductions from baseline were associated with higher atacicept exposure; however, even at the highest exposure range, mean IgG reductions did not exceed 40%. There was no association between serious/severe infections and exposure by PK quartile. Conclusions: Exposure-response modelling indicated robust relationships between atacicept exposure and clinical response or IgG levels, supporting the proposed mechanism of action for atacicept. Atacicept 150 mg weekly SC is likely to provide an effective level of exposure with an acceptable safety profile. There was no evidence of an increased risk of severe or serious infections at higher exposures. Based on these results, the 150 mg dose merits further evaluation.